DNA self-assembly nanoflower reverse P-glycoprotein mediated drug resistance in chronic myelogenous leukemia therapy - Zhao, Pengxuan; Zhong, Yeteng; Pan, Pengcheng; Zhang, Shasha; Tian, Yu; Zhang, Jun; Yi, Guohui; Zhao, Zhendong; Wu, Tiantian (Frontiers in Bioengineering and Biotechnology, 2023)
Chronic myelogenous leukemia (CML) is a clonal myeloproliferative disorder caused by the BCR-ABL chimeric tyrosine kinase. Vincristine (VCR) is widely used in leukemia therapy but is hindered by multidrug resistance (MDR). In this study, we designed a self-assembly DNA nanoflower for the delivery of VCR and P-glycoprotein small interfering RNA (P-gp siRNA). The as-prepared nanoflower had a floriform shape with high loading efficiency of VCR (80%). Furthermore, the nanoflower could deliver VCR and P-gp siRNA into MDR CML cells and induce potent cytotoxicity both in vitro and in vivo, thus overcoming MDR of CML. Overall, this nanoflower is a promising tool for resistant CML therapy.